2016
DOI: 10.1093/femsec/fiw120
|View full text |Cite
|
Sign up to set email alerts
|

Benthic protists: the under-charted majority

Abstract: Marine protist diversity inventories have largely focused on planktonic environments, while benthic protists have received relatively little attention. We therefore hypothesize that current diversity surveys have only skimmed the surface of protist diversity in marine sediments, which may harbor greater diversity than planktonic environments. We tested this by analyzing sequences of the hypervariable V4 18S rRNA from benthic and planktonic protist communities sampled in European coastal regions. Despite a simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 74 publications
(102 reference statements)
11
64
0
Order By: Relevance
“…This has already been demonstrated in assessing microbial eukaryote communities, using the small subunit ribosomal RNA gene (SSU rRNA) as a marker (reviewed in [11], but also see [9,13,18,19]). As yet, we have only skimmed the surface of microbial benthic diversity [20], many basic aspects of experimental design remain poorly known, and the methodologic pipelines are not sufficiently standardised.…”
Section: Introductionmentioning
confidence: 99%
“…This has already been demonstrated in assessing microbial eukaryote communities, using the small subunit ribosomal RNA gene (SSU rRNA) as a marker (reviewed in [11], but also see [9,13,18,19]). As yet, we have only skimmed the surface of microbial benthic diversity [20], many basic aspects of experimental design remain poorly known, and the methodologic pipelines are not sufficiently standardised.…”
Section: Introductionmentioning
confidence: 99%
“…For example, while the broadly targeted V4 primers used here amplify a wide variety of eukaryotic lineages 13,[25][26][27][28][29] , other primers could have amplified additional taxa [30][31][32] (Supplementary Table 1). The resolution power of metabarcoding also has its limits.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, this only works to a limited extent as is shown in the observed high species numbers in high‐throughput metabarcoding studies (e.g., Filker et al ) and also in this study. A commonly applied sequence divergence for ciliate V4 fragments to differentiate between species is 3%, but sometimes also 1%, 2%, and 5% are used (Caron et al ; Nebel et al ; Dunthorn et al ; Weber and Pawlowski ; Balzano et al ; Massana et al ; Forster et al ). Our study suggested that 3% is indeed a proper cutoff for the V4 fragment of most ciliate species, whose intragenomic variability was generally < 3%, while their interspecies variability was higher.…”
Section: Discussionmentioning
confidence: 99%
“…As protist taxa evolve at different rates, there is no consensus on the similarity threshold value. Most commonly, values between 95% and 97% are applied to discriminate between protist taxa (Kammerlander et al ; Massana et al ; Forster et al ; Zhao and Xu , ). USEARCH, in a first step, selects one amplicon from an amplicon pool to serve as a centroid, and then the remaining amplicons are pairwise compared to the centroid (Edgar , ).…”
Section: Materials and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation